PENGEMBANGAN INDUSTRI KREATIF KAFE KOPI DALAM MENINGKATKAN SEKTOR PARIWISATA DI KABUPATEN BONDOWOSO - Yuslinda Dwi Handini (Journal of Tourism and Creativity, 2020)
Abstract This research was conducted to identify the problems faced and what strategies / steps are appropriate in developing the creative coffee cafe industry in improving the tourism sector in Bondowoso Regency. The purpose of this study is to identify the problems faced and describe / explain the development strategy of the creative cafe industry in improving the tourism sector in Bondowos Regency. This research was conducted in Bondowoso Regency, East Java. This research method is descriptive with a qualitative approach. This research uses descriptive analysis. The primary data of this study were obtained from interviews with informants and direct observation of researchers at the research location, while secondary data of this study were obtained from literature sources, the Tourism and Youth Tourism Office in Bondowoso Regency and literature sources. From the results of the research conducted the development of the creative cafe industry Coffee in improving the tourism sector in Bondowoso Regency faces several major problems, namely the first is the HR problem, the second is the capital problem. Third is the problem / obstacle related to the fourth licensing, is the obstacle in maintaining the quality of coffee and packaging or packaging. Next, the fifth obstacle is the lack of market segment of coffee cafes, which is related to marketing. Furthermore, the strategy or step that must be considered by all parties is to increase HR with the synergy between related parties both between the relevant agencies and the managers of the cafe itself. In addition, awareness from the Bondowoso community and Bondowoso coffee business entrepreneurs to continue to be active in developing the creative coffee cafe industry that raised the original Bondowoso coffee in order to improve the tourism sector in Bondowoso district. Keywords: creative industries, tourism, coffee cafes